Вплив факторів маркетингового середовища на ринок молока та молочних продуктів на ринку дитячого харчування - Марчук, Анастасія Олександрівна; Марчук, Анастасия Александровна; Marchuk, Anastasiia (My University, 2018)
UK: У статті розглянуто маркетингове середовище ринку дитячого харчування, проаналізовані сильні та слабкі сторони виробників молочної продукції у розрізі конкурентної боротьби, окреслені загрози та можливості макросередовища та мікросередовища, сформовано альтернативи розвитку ринку дитячого харчування. EN: The article discusses the marketing environment of the baby food market, analyzes the strengths and weaknesses of the dairy producers in the context of competition, outlines the threats and opportunities of the macro and micro-environment, forms alternatives to the development of the market for baby food Experts estimate that the dairy market for children is currently in development. However, strict regulation by the state, the transition to a market economy, which takes place under conditions of very significant environmental impact on enterprises, the emergence of new foreign competitors in the "dairy children" arena and more advanced management methods, predetermine a number of important issues and relevance problems of food security in this market segment. After all, the nutritional status of children is one of the main topics for discussing not only our country, but also the world as a whole. The purpose of the article is to assess the degree of influence of factors of the marketing environment on the efficiency of domestic producers of dairy products on the market for baby food, to reveal their main advantages and disadvantages.
The effect of marketing environment of the dairy market for children
Keywords: маркетингове середовище; виробники; молочна продукція; загрози; фактори макросередовища; можливості; вплив факторів мікросередовища; marketing environment; producers; dairy products; producers; threats; macro-environment factors; opportunities; influence of micro-environment factors